Present knowledge in nutrition. - Marriott, Bernadette P.; Birt, Diane F.; Stallings, Virginia A.; Yates, Allison A. (Academic Press, 2020)
Present Knowledge in Nutrition, Eleventh Edition, provides an accessible, highly readable, referenced, source of the most current, reliable, and comprehensive information in the broad field of nutrition. Now broken into two, separate volumes, and updated to reflect scientific advancements since the publication of its tenth edition, Present Knowledge in Nutrition, Eleventh Edition includes expanded coverage on the topics of basic nutrition and metabolism and clinical and applied topics in nutrition. This volume, Present Knowledge in Nutrition: Clinical and Applied Topics in Nutrition, addresses life stage nutrition and maintaining health, nutrition monitoring, measurement, and regulation, and important topics in clinical nutrition. Authored by an international group of subject-matter experts, with the guidance of four editors with complementary areas of expertise, Present Knowledge in Nutrition, Eleventh Edition will continue to be a go-to resource for advanced undergraduate, graduate and postgraduate students in nutrition, public health, medicine, and related fields; professionals in academia and medicine, including clinicians, dietitians, physicians, and other health professionals; and academic, industrial and government researchers, including those in nutrition and public health. --